Rekonstruksi Kritik Sanad dan Matan dalam Studi Hadis - Suryadi Suryadi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
As part of the science , the study of hadith needs to get development and innovation. Therefore, it is necessary for the reconstruction of critical studies chains and Matan. This article will discuss the possibility of reconstruction critical studies chains and Matan hadith. Sanad criticism (kritik sanad) needs to be developed on the use of data derived from the book in addition to the books of Rijal that conclusion on levels of integrity and intellectual person can be formulated more accurately and emphasize objectivity. Meanwhile, critical studies of matan also need to be developed by applying the hermeneutical method in understanding the text of the Prophet, in order to reject the mindset of tasâhul in the weakness of traditions as well as traditions that gave birth to the meaning of its as shâlih likulli zamân wa makân.[Sebagai bagian dari ilmu pengetahuan, studi hadis perlu mendapatkan pengembangan dan inovasi. Oleh karena itu, diperlukan adanya rekonstruksi atas kajian kritik sanad dan matan. Artikel ini akan membahas kemungkinan rekonstruksi kriitk sanad dan matan hadis.  Kritik sanad perlu dikembangkan pada pemanfaatan data-data yang berasal dari kitab selain kitab-kitab rijâl agar konklusi atas kadar integritas dan intelektualitas seseorang bisa diformulasikan secara lebih akurat dan menekankan aspek objektivitas. Sementara itu, kritik matan juga perlu dikembangkan dengan menerapkan metode hermenetika dalam memahami teks Nabi, supaya bisa menolak pola pikir tasâhul dalam pendhaifan hadis sekaligus juga melahirkan makna hadis yang shâlih likulli zamân wa makân.]